The evaluation on data mining methods of horizontal bar training based on BP neural network - Zhang, Y.; Liu, S. (MATEC Web of Conferences, 2015)
With the rapid development of science and technology, data analysis has become an indispensable part of people`s work and life. Horizontal bar training has multiple categories. It is an emphasis for the re-search of related workers that categories of the training and match should be reduced. The application of data mining methods is discussed based on the problem of reducing categories of horizontal bar training. The BP neural network is applied to the cluster analysis and the principal component analysis, which are used to evaluate horizontal bar training. Two kinds of data mining methods are analyzed from two aspects, namely the operational convenience of data mining and the rationality of results. It turns out that the principal component analysis is more suitable for data processing of horizontal bar training.